Gathering insights on the forest from the trees: A new metric for financial conditions - Scott Brave; R. Andrew Butters (Federal Reserve Bank of Chicago, 2010)
By incorporating the Harvey accumulator into the large approximate dynamic factor framework of Doz et al. (2006), we are able to construct a coincident index of financial conditions from a large unbalanced panel of mixed frequency financial indicators. We relate our financial conditions index, or FCI, to the concept of a financial crisis using Markov-switching techniques. After demonstrating the ability of the index to capture crisis periods in U.S. financial history, we present several policy-geared threshold rules for the FCI using Receiver Operator Characteristics (ROC) curve analysis.
Keywords: G01; G17; C22; 330; financial crisis; financial conditions; dynamic factor; EM algorithm; Harvey accumulator; ROC curve; Markov-switching